The effect of petrol and diesel on high density polyethylene (HDPE) and cross-linked HDPE bottles: tensile and thermal properties analysis - Chen, Chan Hoong; Wan Abdul Rahman, Wan Aizan; M., Mohd. Nazrul (2004)
The effect of petrol and diesel on High Density Polyethylene (HDPE) and cross-linked HDPE bottles (XLHDPE) are studied according to ISO175: 1999. The HDPE and cross-linked HDPE bottles were prepared by blow molding technique. The bottles were immersed in petrol and diesel for 1 day, 1 week, 8 weeks and 16 weeks at temperatures 23°C and 70°C. Tensile test was carried out to determine the modulus, tensile strength and elongation at break. The degradation of HDPE and cross-linked HDPE was monitored by DSC. The tensile properties results show that the rate of degradation for petrol immersion > diesel immersion and temperature 70°C > 23°C for both HDPE and XLHDPE. The cross-linked HDPE is more stable to petrol and diesel attack compared to HDPE. DSC shows that a small changes in crystallinity and melting point for both samples. The melting behavior of exposed samples is almost constant.